2015
DOI: 10.1002/eat.22379
|View full text |Cite
|
Sign up to set email alerts
|

Favorable effects of clearly defined interventions by parents at the start of treatment of adolescents with restrictive eating disorders

Abstract: Decisive parental management of eating disturbed behaviors at the start of treatment of adolescents with ED promotes later clinical outcome. The finding supports the view that family based therapies are effective in adolescent ED. Results has to be followed up for evaluation of the long term effects of this type of intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
0
24
0
3
Order By: Relevance
“…The prediction of favourable outcome of AN by rapid early weight gain [ 40 ] is applicable also in the present OSFEDr population. We have previously shown that the weight gain at start of treatment is promoted by a consistent intervention of the parents [ 24 ]. The effect of the interventions of the parents to promote early weight gain is now extended to predict a favourable overall outcome of the ED across a wide BMI range.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prediction of favourable outcome of AN by rapid early weight gain [ 40 ] is applicable also in the present OSFEDr population. We have previously shown that the weight gain at start of treatment is promoted by a consistent intervention of the parents [ 24 ]. The effect of the interventions of the parents to promote early weight gain is now extended to predict a favourable overall outcome of the ED across a wide BMI range.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesised that early rapid weight gain and absence of weight suppression at the one-year follow-up would be associated with a favourable outcome. We also hypothesised that the preliminary results of our previous study [ 24 ] would be confirmed in a larger cohort, i.e. the early interventions performed by the parents would be reflected in a favourable outcome.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Assessment was then reviewed and completed and instruments administered. The assessment procedure has previously been described in detail (Rosling, 2013;Månsson, Parling, & Swenne, 2015). The protocol was approved by the Ethics Committee of Uppsala University.…”
Section: Methodsmentioning
confidence: 99%